2013
DOI: 10.1007/s00404-013-2927-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of three different surgical approaches in repairing paravaginal support defects: a comparative trial

Abstract: The effectiveness of paravaginal repair procedure is similar whether the abdominal or vaginal approaches were adopted in patients with anterior compartment prolapse due to paravaginal support defects. In our experience, the laparoscopic approach was associated with the least favourable outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…In women with advanced POP, anatomical distortion may alter US measurements as a result of paravaginal defects. A defect in the lateral suspension of the bladder could lead to an enlarged transverse diameter, and thus volume estimation using the available formulae may not be accurate enough to be used in clinical practice for these women.…”
Section: Discussionmentioning
confidence: 99%
“…In women with advanced POP, anatomical distortion may alter US measurements as a result of paravaginal defects. A defect in the lateral suspension of the bladder could lead to an enlarged transverse diameter, and thus volume estimation using the available formulae may not be accurate enough to be used in clinical practice for these women.…”
Section: Discussionmentioning
confidence: 99%
“…It is not possible to study every clinical outcome with a randomised trial. Multiple, independent cohort studies may be '' good enough'' to justify adding/omitting the new surgery to/from our armamentarium [27].…”
Section: Discussionmentioning
confidence: 99%
“…Repair of PVD is particularly important in preventing postoperative recurrence of anterior vaginal wall prolapse, as they account for 60%-80% of cases. 22 Additionally, folding the levator ani muscle through several Ushaped sutures between longitudinal incisions increases the support of the posterior vaginal wall at the second level. Mikos et al 14 found that simultaneous folding of the levator ani muscle at the time of closure was effective in preventing postoperative recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we used longitudinal sutures to close the anterior and posterior vaginal walls, which increases the repair of PVD. Repair of PVD is particularly important in preventing postoperative recurrence of anterior vaginal wall prolapse, as they account for 60%–80% of cases 22 . Additionally, folding the levator ani muscle through several U‐shaped sutures between longitudinal incisions increases the support of the posterior vaginal wall at the second level.…”
Section: Discussionmentioning
confidence: 99%